2008
DOI: 10.5539/mas.v2n2p117
|View full text |Cite
|
Sign up to set email alerts
|

Oxovanadium (IV) Dipicolinate: Structure Nucleolytic and Anticancer Property

Abstract: Diaqua(dipicolinato)oxovanadium (IV) ethanol solvate crystallizes in the triclinic space group P1. The complex was characterized by FTIR, elemental analysis, thermal gravimetric analysis, and solution visible spectral analysis. The complex alone cleaved DNA in the absence of hydrogen peroxide and its nucleolytic efficiency is greater than that of VOSO 4 . Its nucleolytic efficiency is affected by the choice of buffer used and pH. DNA cleavage can be inhibited by DMSO, NaN 3 and catalase, implying involvement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Vanadium complex compounds are used as catalysts in industrial production of synthetic rubbers, elastomers and polyethylene [31]. However, in our case, special attention was given to the dipicolinate complex of oxovanadium(IV), due to its widely described physicochemical and biological properties such as combating diabetes type I and II [32], cell metabolism [33], antioxidant properties [34], plasmid DNA cleavage, chromosomal aberrations and use in anticancer therapy [35,36]. Thorn et al have reported the application of V-dipic complexes as: [VO(dipic)(i-PrO)], [VO(dipic)(pinme)], [VO(dipic)(dpheol)] and analogs in stoichiometric aerobic oxidation of isopropanol and other alcohols as lignin models [37].…”
Section: Introductionmentioning
confidence: 99%
“…Vanadium complex compounds are used as catalysts in industrial production of synthetic rubbers, elastomers and polyethylene [31]. However, in our case, special attention was given to the dipicolinate complex of oxovanadium(IV), due to its widely described physicochemical and biological properties such as combating diabetes type I and II [32], cell metabolism [33], antioxidant properties [34], plasmid DNA cleavage, chromosomal aberrations and use in anticancer therapy [35,36]. Thorn et al have reported the application of V-dipic complexes as: [VO(dipic)(i-PrO)], [VO(dipic)(pinme)], [VO(dipic)(dpheol)] and analogs in stoichiometric aerobic oxidation of isopropanol and other alcohols as lignin models [37].…”
Section: Introductionmentioning
confidence: 99%